Embarazo a termino mas trabajo de parto eutocico simple - Reyes Goyes, Génesis Andrea (2018)
This work is based on a patient with a pregnancy at the end of 40 weeks more labor which ends in a normal delivery. According to the information given to pregnant women about prenatal surveillance and control, it is good and adequate. Since there are now health programs, in which we have implemented modules of maternal and child care, to detect and correct opportunely some abnormalities in the stages of pregnancy. What is the correct asepsis during the months of pregnancy to finish it without problem. As for childbirth we know that this is a physiological process in which the pregnant woman ends her pregnancy at term, in which psychological and sociocultural factors are involved. Its beginning is spontaneous, evolves and ends without complications, ends with the delivery and does not imply any more intervention